ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MAHASISWA INSTITUT AGAMA ISLAM SAHID INAIS BOGOR MENABUNG DI BANK BNI SYARIAH - Heri Ilham Nasrudin; Tubagus Rifqy Thantawi; Ermi Suryani (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2021)
Abstract The results of this study are to find out what factors influence and how much interest in Bank BNI Syariah. The benefits of increasing knowledge and getting to know what products are in BNI Syariah for INAIS students and increasing funding and credit at Bank BNI Syariah, quantitative methods with deductive theory, with descriptive statistics online questionnaires to test data, nonprobability sample research sampling with purposive sampling Tabhacic & Fiedell techniques and approaches. This research is supported by a thesis from Yayan Fauji 2010 which states that what influences the intention to save in Islamic banking is the profit sharing ratio and the quality of Islamic banking products. Some other findings that are not in line with this research regarding the factors that influence the intention to save at Islamic Banks, The 2018 Uniyanti's thesis states that what influences the intention to save at Islamic Banks is the factor of religion and pocket money income. . The results of this study used a linear regression test, partial T test, then t-table with a two-way test and α = 5% (0.05) is 1.97944. Then t count on the variable X1 Religion 1.293, X2 Knowledge 0.984, X3 Economic Ability of Parents 0.361, Promotion of Islamic Banks 1.367, Existence of Facilities 1.758, and Administrative Costs 1.549 less than t table. Thus Ho's decision is accepted by Ha is rejected. This means that there is no influence and not significant (not real) from the 6 variables. The influence of the 7 variables is only the profit sharing ratio of 2.389 so that Tcount is greater than Ttable. So thus Ho's decision is rejected and Ha is accepted. This means that there is significant influence and profit sharing ratio (real) on students' interest in saving at Bank BNI Syariah. Looking at the partial t test with a constant B of 1.850 which affects the interest in saving INAIS students at Bank BNI Syariah is the profit sharing ratio variable with a value of 0.226 using a two-way test α = 5% (0.05) of 1.97944, then the Constant B+ value If the ratio value is around 2.076, then the number of INAIS students who are interested in Bank BNI is around 0.02%, so that 9.93% of students are not interested in saving at Bank BNI Syariah.